Functional analysis of Thermus thermophilus transcription factor NusG - Sevostyanova, Anastasiya (Oxford University Press, 2010)
Transcription elongation factors from the NusG family are ubiquitous from bacteria to humans and play diverse roles in the regulation of gene expression. These proteins consist of at least two domains. The N-terminal domains directly bind to the largest, β′ in bacteria, subunit of RNA polymerase (RNAP), whereas the C-terminal domains interact with other cellular components and serve as platforms for the assembly of large nucleoprotein complexes. Escherichia coli NusG and its paralog RfaH modify RNAP into a fast, pause-resistant state but the detailed molecular mechanism of this modification remains unclear since no high-resolution structural data are available for the E. coli system. We wanted to investigate whether Thermus thermophilus (Tth) NusG can be used as a model for structural studies of this family of regulators. Here, we show that Tth NusG slows down rather than facilitates transcript elongation by its cognate RNAP. On the other hand, similarly to the E. coli regulators, Tth NusG apparently binds near the upstream end of the transcription bubble, competes with σ(A), and favors forward translocation by RNAP. Our data suggest that the mechanism of NusG recruitment to RNAP is universally conserved even though the regulatory outcomes among its homologs may appear distinct.